Effects of winter nutrition level on cow and calf performance - R.R. Schalles; C.L. Drake; G. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1969)
Cow and calf performance under four winter nutritional levels was evaluated, using 61 purebred Polled and high grade Hereford cows randomly allotted to obtain approximately equal pregnant and open cows in each group. The cows were 1.0 be 4.5 years old, except for two older ones. Average calving date was mid April. Forty-five live calves were born. They were weighed within 24 hours after birth and at monthly intervals from June to November calf was born dead. Cows were weighed each month and rotated among four native bluestem pastures during the entire year. All calves were graded and weaned at the last weighing.
Keywords: Cattlemen& #x27; s Day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station); 529; Beef; Winter nutrition; Cow-calf performance; Bluestem pastures